2021
DOI: 10.1210/clinem/dgab107
|View full text |Cite
|
Sign up to set email alerts
|

Dysnatremia is a Predictor for Morbidity and Mortality in Hospitalized Patients with COVID-19

Abstract: Background Dysnatremia is an independent predictor of mortality in patients with bacterial pneumonia. There is paucity of data about the incidence and prognostic impact of abnormal sodium concentration in patients with coronavirus disease 19 (COVID-19). Methods This retrospective longitudinal cohort study, including all adult patients who presented with COVID-19 to two hospitals in London over an 8-week period, evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
133
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(166 citation statements)
references
References 47 publications
27
133
4
2
Order By: Relevance
“…In addition to CRP and HGB, calcium, potassium, sodium, WBC, neutrophil, lymphocyte cell count and Vitamin-D are extensively discussed in the literature (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). All of these factors except Vitamin D and potassium show significant differences between non-surviving and surviving patients in Table 3 and are discussed in the literature, which confirm our findings and indicate dysregulation in COVID-19 patients.…”
Section: Discussionsupporting
confidence: 87%
“…In addition to CRP and HGB, calcium, potassium, sodium, WBC, neutrophil, lymphocyte cell count and Vitamin-D are extensively discussed in the literature (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). All of these factors except Vitamin D and potassium show significant differences between non-surviving and surviving patients in Table 3 and are discussed in the literature, which confirm our findings and indicate dysregulation in COVID-19 patients.…”
Section: Discussionsupporting
confidence: 87%
“…Hyponatremia at admission was so far independently associated with male sex, old age [73], presence of several comorbidities and diagnosis of severe pneumonia on chest X-ray [74]. Moreover, poorer clinical outcomes and higher mortality were reported in COVID-19 patients with hyponatremia [75].…”
Section: Hyponatremia-syndrome Of Inappropriate Antidiuretic Hormone Secretion (Siadh)mentioning
confidence: 99%
“…Recent literature suggests that hyponatraemia in COVID-19 patients is at least as common as in other pneumonia cases. Berni et al showed a prevalence of hyponatremia of 22.9%, which is in the range of most other literature showing a prevalence of around 20-30% [5][6][7]9 . An even higher prevalence of 40% has been shown in a large study in 10'000 patients across 13 hospitals in a New York health system 4 .…”
Section: What To Look At If Patients With Hyponatremia Are Admitted To the Hospital With Acute Infection With Covid-19mentioning
confidence: 62%
“…Initial data suggested that hypernatraemia, in contrast to other critically ill patients, is not a risk factor for severe mortality in COVID-19 25 . More recent data, however, show that hypernatraemia is associated with adverse outcomes and mortality, similar to other critically ill patients [4][5][6][7] .…”
Section: Acute Infection With Suspected or Confirmed Covid-19mentioning
confidence: 67%
See 1 more Smart Citation